0

# Can someone solve this equation for me stomped

2x^2 +14x =88

The solution or solutions is (are) x=?

### 5 Answers by Expert Tutors

4.9 4.9 (219 lesson ratings) (219)
0
Hey Brandon -- cut in half 2x^2 +14x =88 ... x^2 +7x -44 =0 ... try -4x11 to get +7
(x+11)(x-4) =0 ... x= -11 or 4 Regards, sir :)
Arthur D. | Effective Mathematics TutorEffective Mathematics Tutor
5.0 5.0 (7 lesson ratings) (7)
0
2x^2+14x=88
subtract 88 from both sides
2x^2+14x-88=0
divide both sides of the equation by 2 to get x^2+7x-44=0
the equation is in the form ax^2+bx+c=0
a and b are both odd, (1 and 7)
therefore c(-44) must be factored into an odd number times an even number, NOT an even times an even
therefore you can't use 2 and 22, you must use 1 and 44 or 4 and 11(disregarding signs for the moment)
does adding 11 and 4 or subtracting 11 and 4 give you 7 ?  YES, 11-4=7
-44=(4)(-11) or (-4)(11)
the coefficient of x must be +7, so you can't  use 4 and -11(-11+4=-7)
you must use -4 and 11 because 11+(-4)=7
therefore you get 2(x+11)(x-4)=0
x+11=0 and x-4=0
x=-11 and x=4

Kirill Z. | Physics, math tutor with great knowledge and teaching skillsPhysics, math tutor with great knowledge...
4.9 4.9 (174 lesson ratings) (174)
0
First, divide both side by 2. You will get:

x2+7x=44 or
x2+7x-44=0;

You may use factoring. Two factors that multiply to get -44 are -11 and 4. Their sum shall be equal to coefficient in front of x, but with opposite sign. Indeed, -11+4=-7, just as it should be.

So the trinomial can be factored as follows:
x2+7x-44=(x+11)(x-4); If (x+11)(x-4)=0 then x=-11 or x=4.
Don L. | Don - Math/Science Tutor from Elementary School to College levelDon - Math/Science Tutor from Elementary...
4.9 4.9 (80 lesson ratings) (80)
0

2x^2 +14x =88

2x^2 +14x - 88 = 0

2(x^2 +7x - 44) = 0

2(x + 11)(x - 4) = 0

x = -11 or x = 4
Marietta G. | Versatile EducatorVersatile Educator
4.8 4.8 (186 lesson ratings) (186)
0
2x2 +14x =88

1. First subtract 88 from both sides so that the equation is equal to 0.
2x2 +14x - 88 = 0

2. Find the Highest Common Factor (HCF) that can be divided into each term
in the trinomial.
2 (x2 +7x - 44) = 0

3. Factor the remaining trinomial.
2 (x2 +7x - 44) = 0
a. Find the pairs of factors of the third term -44 = -4,11 or 4, -11;
-2,22 or 2, -22; -1,44, 1,-44;
b. Choose the pair of factors that when added together give +7,
the coefficient of the middle term. These are -4 and +11.
2 (x - 4)( x + 11) = 0

4. Finally use the zero product property to solve the equation.
x - 4 = 0     |      x + 11 = 0
x = 4          |       x = -11